A case study on social intrapreneurial ventures by corporations within the Philippines - Ang, Benedict D. (Animo Repository, 2021)
This research explores social intrapreneurial ventures by corporations within the Philippines. Social intrapreneurship is driven by social and environmental values, going beyond the interest of private individuals and organizations through promoting various initiatives that intend to address social and/or environmental challenges while creating a revenue stream for their organization (Frederick, 1960). Corporations possess enormous capabilities, influence, and resources that may leave a large impact on its stakeholders. This study will utilize a qualitative multiple-embedded case study research through the perspective of dynamic capabilities theory and instrumental stakeholder theory. This study was conducted with respective existing social intrapreneurial ventures from Unilever Philippines and San Miguel Corporation. We found that the cases exhibited existing themes and also new themes that emerged from Teece’s dynamic capabilities, all of which had high interaction with instrumental stakeholders. With the insights gained from this research, purpose-driven organization may serve as a platform for their social intrapreneurial venture’s dynamic capabilities, along with heavy interaction with instrumental stakeholders, to recur as there are many new opportunities available to sense, seize, and transform towards the intended outcome of creating social value.